Common Considerations for Genotoxicity Assessment of Nanomaterials - Elespuru, Rosalie K.; Doak, Shareen H.; Collins, Andrew R.; Dusinska, Maria; Pfuhler, Stefan; Manjanatha, Mugimane; Cardoso, Renato; Chen, Connie L. (Frontiers in Toxicology, 2022)
Genotoxicity testing is performed to determine potential hazard of a chemical or agent for direct or indirect DNA interaction. Testing may be a surrogate for assessment of heritable genetic risk or carcinogenic risk. Testing of nanomaterials (NM) for hazard identification is generally understood to require a departure from normal testing procedures found in international standards and guidelines. A critique of the genotoxicity literature in Elespuru et al., 2018, reinforced evidence of problems with genotoxicity assessment of nanomaterials (NM) noted by many previously. A follow-up to the critique of problems (what is wrong) is a series of methods papers in this journal designed to provide practical information on what is appropriate (right) in the performance of genotoxicity assays altered for NM assessment. In this “Common Considerations” paper, general considerations are addressed, including NM characterization, sample preparation, dosing choice, exposure assessment (uptake) and data analysis that are applicable to any NM genotoxicity assessment. Recommended methods for specific assays are presented in a series of additional papers in this special issue of the journal devoted to toxicology methods for assessment of nanomaterials: the In vitro Micronucleus Assay, TK Mutagenicity assays, and the In vivo Comet Assay. In this context, NM are considered generally as insoluble particles or test articles in the nanometer size range that present difficulties in assessment using techniques described in standards such as OECD guidelines.